Mutual Effect Modification between Insulin Resistance and Endothelial Dysfunction in Predicting Incident Heart Failure in Hypertensives - Maria Perticone; Raffaele Maio; Simona Gigliotti; Ermal Shehaj; Alfredo Francesco Toscani; Antonella Capomolla; Ginevra Fabiani; Angela Sciacqua; Francesco Perticone (Biomedicines, 2023)
Insulin resistance and endothelial dysfunction are associated with heart failure (HF). Our objective was to investigate whether endothelial dysfunction and insulin resistance are independent predictors of incident HF and if a possible interaction exists between them. We enrolled 705 white never-treated hypertensives. Endothelium-dependent vasodilation was investigated by intra-arterial infusion of acetylcholine. During the follow-up [median: 117 months (range: 31–211)], we documented 223 new cases of HF (3.3 events/100 patient-years). We stratified the study population into progressors and non-progressors; progressors showed an older age and a higher prevalence of females, as well as higher mean values of baseline glucose, insulin, homeostasis model assessment (HOMA), creatinine, and high-sensitivity C-reactive protein (hs-CRP), whereas the estimated glomerular filtration rate (e-GFR) and endothelium-dependent vasodilation were lower. In the multiple Cox regression analysis, serum hs-CRP (HR = 1.362, (95% CI = 1.208–1.536), HOMA (HR = 1.293, 95% CI = 1.142–1.465), maximal acetylcholine (Ach)-stimulated forearm blood flow (FBF) (100% increment, HR = 0.807, 95% CI = 0.697–0.934), and e-GFR (10 mL/min/1.73 m2 increment, HR = 0.552, 95% CI = 0.483–0.603) maintained an independent association with incident HF. HOMA and endothelial dysfunction interact between them in a competitive manner (HR = 6.548, 95% CI = 4.034–10.629), also showing a mutual effect modification. Our findings demonstrate that both endothelial dysfunction and HOMA are independent and strong predictors of incident HF in hypertensives, these two risk factors interact between them with a competitive mechanism.